Using an online digital wall board to promote student activity in a library course - Ingunn Rødland (Nordic Journal of Information Literacy in Higher Education, 2020)
The content in library courses is highly relevant for students to perform well in their studies. But the material taught by librarians is usually not part of the curriculum and will not be tested directly in summative assessments. Students therefore tend to be passive and uninvolved in these lectures. The aim of this study was to investigate whether a digital online tool can help students to be more active and engaged. The proportion of students who used this tool to interact with the lecturer varied slightly among the different classes in the study, but the participation rate was relatively high overall. A lesson learned for later use of this kind of tool is that it is important to have planned how students should use the tool, and how the teaching must be organized to make that use possible.